Electrochemistry of Copper in Polyacrylic Acid: The Electrode Mechanism and Analytical Application for Gaseous Hydrogen Peroxide Detection - Stojanov, Leon; Rafailovska, Angela; Jovanovski, Vasko; Mirceski, Valentin (Journal of physical chemistry. C, 2022)
Electrode reaction of copper(II) reduction in an aqueous solution of polyacrylic acid (PAA) is studied by means of cyclic staircase and square-wave voltammetry to establish a basis for an electrochemical sensor for gaseous hydrogen peroxide detection. It has been determined that the reduction mechanism at a glassy carbon electrode follows a two-step, consecutive electron transfer reaction scheme of Cu2+ to the final copper solid deposit, via the formation of the intermediate Cu+ ions, which are subject to a fast disproportionation reaction. Experimental data have been supported by theoretical considerations and simulations based on EC’E electrode mechanism, where E designates an electrode reaction, whereas C’ is a homogeneous regenerative chemical reaction. Estimated thermodynamic and kinetic data of the electrode mechanism suggest stabilization of the intermediate Cu+ form by PAA in comparison with a pure aqueous medium. Commercially available screen-printed carbon electrodes were covered with a film of 1% (mass percent) of aqueous PAA solution containing Cu2+ ions, which proves to be a promising platform for gaseous H2O2 detection, where the Cu2+/Cu+ couple serves as a redox mediator for H2O2 reduction, with a limit of detection at a sub-μg dm–3 concentration level in the gas phase.